2017
DOI: 10.3389/fnins.2017.00334
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Prefrontal/Frontal Brain Stimulation Is Not Effective in Modulating Food Reappraisal Abilities or Calorie Consumption in Obese Females

Abstract: Background/Objectives: Previous studies suggest that non-invasive transcranial direct current stimulation (tDCS) applied to the prefrontal cortex modulates food choices and calorie intake in obese humans.Participants/Methods: In the present fully randomized, placebo-controlled, within-subject and double-blinded study, we applied single sessions of anodal, cathodal, and sham tDCS to the left dorsolateral prefrontal cortex (DLPFC) and contralateral frontal operculum in 25 hungry obese women and investigated poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 83 publications
(160 reference statements)
0
35
0
Order By: Relevance
“…Controversial findings due to methodological differences deserve more research in this field. In addition, the discrepancy between the study by Grundeis et al 25 and other more positive findings 24 demands further studies, for example, combining repetitive DCS instead of just one single session. In this regard, Ljubisavljevic et al, using repeated tDCS, reduced craving even 30 days after the intervention.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Controversial findings due to methodological differences deserve more research in this field. In addition, the discrepancy between the study by Grundeis et al 25 and other more positive findings 24 demands further studies, for example, combining repetitive DCS instead of just one single session. In this regard, Ljubisavljevic et al, using repeated tDCS, reduced craving even 30 days after the intervention.…”
Section: Discussionmentioning
confidence: 78%
“… 17 , 69 Generally, these studies have found a reduction in the calorie intake per day, mood improvements, a reduction in ED cognitions, and a reduction in food craving. Nevertheless, the study by Grundeis et al 25 does not support the notion of prefrontal/frontal DCS as a promising treatment option for obesity. Controversial findings due to methodological differences deserve more research in this field.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations